2009
DOI: 10.1007/s11064-009-0026-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Central Dopaminergic System in Acute and Chronic Unpredictable Stress Models in Rats

Abstract: We aimed to evaluate the response of dopaminergic system in acute stress (AS) and chronic unpredictable stress (CUS) by measuring dopamine (DA) levels, its receptor densities in the frontal cortex, striatum, hippocampus, amygdala and orbito-frontal cortex regions of rat brain, and investigated the corresponding behavioral locomotor changes. Involvement of D(1) receptor was also examined during AS and CUS using A 68930, a D(1) selective agonist. Rats were exposed to AS (single immobilization for 150 min) and CU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…In contrast, acute stress mostly enhanced and chronic stress decreased central dopamine and serotonin levels in a region-specific manner (Ahmad et al, 2010; Rasheed et al, 2010). In the prefrontal cortex, dopamine was increased by stressors like acute swim stress (H-FSS mice) or by acute restraint stress (Ahmad et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, acute stress mostly enhanced and chronic stress decreased central dopamine and serotonin levels in a region-specific manner (Ahmad et al, 2010; Rasheed et al, 2010). In the prefrontal cortex, dopamine was increased by stressors like acute swim stress (H-FSS mice) or by acute restraint stress (Ahmad et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Within the frontal cortex, most studies report that CMS results in a reduction in DA and its primary metabolites 3,4-dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA), or a decreased turnover of DA indicative of reduced DA signaling (Sheikh et al, 2007; Rasheed et al, 2008, 2010; Ahmad et al, 2010; Shi et al, 2010; Dang et al, 2009a,b; Harro et al, 2001); [only in females (Dalla et al, 2008)]. Nonetheless, there also exist several reports of no effect of CMS on DA signaling (Tannenbaum and Anisman, 2003; Johnson and Yamamoto, 2009, 2010; Patterson et al, 2010; Haidkind et al, 2003; Di Chiara et al, 1999) and one report of increased DA levels in the frontal cortex following CMS (Yi et al, 2008).…”
Section: Neurochemical Systemsmentioning
confidence: 99%
“…Similarly, repeated immobilisation stress increases D 2 receptor binding in the NAcc when animals are single housed after stress, whereas pair-housing after stress is associated with increased D 2 binding in the dorsal striatum [71] . On the other hand, in several studies no chronic stress-associated change in the functional state of D 2 has been observed, either in the NAcc or in the dorsal striatum [55,56,63,64] . Considering the stress !…”
Section: Discussionmentioning
confidence: 88%
“…This finding is in line with studies that showed a decrease in basal extracellular dopamine levels in the NAcc shell [22,54] , a decreased number of dopamine transporter binding sites [54] as well as an increase in D 1 receptor-specific radioligand binding and V max of D 1 agonist-stimulated adenylyl cyclase in the NAcc, but not in the striatum, of animals submitted to chronic stress [54,55] . That this is a regionally specific effect is suggested by findings that neither acute nor chronic stress changed D 1 and D 2 receptor expression levels in the amygdala [56] . In contrast, chronic antidepressant administration decreases D 1 receptorspecific binding, cAMP accumulation [57][58][59] and spontaneous firing rates of dopaminergic neurons in the NAcc [60] , and elevates D 1 but not D 2 receptor gene expression in the NAcc [61] .…”
Section: Discussionmentioning
confidence: 99%